Governance Innovations for forest ecosystem service provision – Insights from an EU-wide survey. Issue 132 (June 2022) - Mann, Carsten; Loft, Lasse; Hernández-Morcillo, Mónica; Primmer, Eeva; Bussola, Francesca; Falco, Enzo; Geneletti, Davide; Dobrowolska, Ewelina; Grossmann, Carol M.; Bottaro, Giorgia; Schleyer, Christian; Kluvankova, Tatiana; et al.
Abstract: This paper analyses the occurrence of governance innovations for forest ecosystem service (FES) provision in the forestry sector in Europe and the factors that influence innovation development. Based on a European-wide online survey, public and private forest owners and managers representing different property sizes indicate what type of governance innovation activities they engage in, and why. To investigate forestry innovations as systems, the analysis focuses on biophysical, social and technical factors influencing innovation development. The results of our exploratory quantitative analysis show that most innovation activities identified are largely oriented towards biomass production. Accordingly, most forest owners implement efficiency-driven optimisation strategies for forest management and technological improvement for provisioning service supply, to generate income. In contrast, the provision of regulating and cultural services is not yet a prominent part of forestry innovation activities.Reasons are rooted in a market-oriented economic rationale focusing on timber production, a lack of financial resources to compensate for other FES provisions or institutions to provide backup and security to forest owners and managers for engaging in innovation development. Given that the provision of a wide range of FES is a politically well-established objective for forest management in Europe, a strategy is needed that helps to align actors and sectors for supporting and co-financing related forest management approaches and business models. The current revision of the forest related policy framework on EU level under the EU Green deal poses a window of opportunity for better fostering novel governance approaches for more sustainable FES provision. Highlights: Sustainable provision of FES require a system- and innovation-based perspective. Most innovation activities are characterised by optimisation strategies for biomass provision. Lacking resources and institutions prevent foresters to engage in innovation activities. New forms of communication, cooperation and financing are needed for providing non-wood FES. Current revisions of EU policy frameworks pose possibilities for novel forms of FES governance.